A Texas Baptist Power Struggle : the Hayden Controversy. (University of North Texas Press, 2005)
This is the story of how one man, Samuel Augustus Hayden, almost destroyed the newly organized Baptist General Convention of Texas (BGCT) before it could take root. After a failed takeover attempt of the BGCT in the late nineteenth century, Hayden was expelled from the state body. In turn, he created a rival organization, the Baptist Missionary Association (BMA), which continued to fight perceived oppression by the BGCT. Baptists in Texas were forced to take sides in the struggle, which came to a dramatic conclusion on a train bound for the Southern Baptist Convention, when Hayden and his rival scuffled over a pistol.